Turbulent Times Management Tolerance and Personal Power of Secondary School Administrators - Baliton, Fructuoso C. (JPAIR Institutional Research, 2016)
Turbulence refers to both internal and external changes within organizations, and demands from their environments. Power involves the potential to influence others, both in what they do and how they feel about something. This descriptive survey-correlation method of research aimed to determine whether the tolerance for managing in turbulent times of secondary school administrators of Leyte, Philippines were related to their personal power profile. A set of data-gathering questionnaire, composed of two parts was utilized. The results showed that the respondents have to work on improving their tolerance for managing in turbulent times and must have something likely to characterize in the world of work into the next century. Expert Power is the dimension of power that is subscribed by them, which is considered to be their behavior in work organizations since as suggested by the results, the respondents prefer to influence others by employing this particular form of power. Chi-square established that the non-significant relationships between the two variables imply that being ready to face turbulence and change, has nothing to do with their personal power profile or how they prefer to influence others.